Critic Towards Legislative Candidates in #UNBOXINGCALEG - Fathul Qorib; Afriansyah Afriansyah; Suprihatin Suprihatin (Jurnal Nomosleca, 2020)
Instagram is one of the most used social media in Indonesia. In 2019, Indonesian Instagram users reached 56 million, Indonesia ranked 4th for country with the most Instagram users around the world. Along with the massive users in Indonesia, Instagram is used as a campaign and promotion media. One of the most popular campaign was some videos with #unboxingcaleg hashtag driven by TemanRakyat.Id. The videos criticized legislative candidates with various signs and symbols. This study aims to reveal these criticisms using Ferdinand de Saussure's semiotics theory. First,  researcher will identify the signifier elements (marker), and then reveal its signified. The qualitative method is used to obtain the depth interpretation of the video. As a result, researcher found patterns of signaling systems that express criticism of legislative candidates, as follow: First, candidates are associated as liars because they always make promises they never kept. Both candidates are represented as corruptors / former corruptors who are not ashamed to participate in election again. Third, candidates are considered lazy since they never finished the draft of Indonesian Law. Fourth, candidates are identified as shaping their public image with planned lies. The videos with #unboxingcaleg are considered to carry out some campaigns to make smart voters choose wisely since both candidates have a lot of dishonorable attitudes. Keywords: Representation, legislative candidates and #unboxingcaleg.Keywords : Legislative Candidates, Temanrakyat.Id, Unboxingcaleg,